Preparation of Sea-buckthorn Oil Microcapsule Composite Film and the Preservation Effect of Hand-grabbed Mutton - Bingbing ZHANG; Guishan LIU; Delang XIE; Haiyang MA; Yang LI; Fang MA; Xiaojun LI; Qingqing CAO; Xiaoxue LI; Qian ZHANG (Shipin gongye ke-ji)
In order to explore the preservation effect of microcapsule composite film with sea-buckthorn oil on hand-grabbed mutton, this study used gelatin/acacia to coat sea-buckthorn oil, and prepared microcapsule composite film with sea-buckthorn oil using gelatin as membrane substrate and glycerin as plasticizer. The mechanical properties, surface morphology and antioxidant and antibacterial activities of the composite film were measured, and the film was fitted on the surface of hand-grabbed mutton. The effects of composite membrane on color, pH, weight loss, TVB-N, total number of bacterial colonies and sensory indexes were analyzed to evaluate the fresh-keeping effect of hand-grabbed mutton. Results showed that the embedding rate and yield of sea buckthorns oil microcapsules were 88.94% and 76.28%, respectively, and the optimum conditions for preparing the membrane were 6 g/100 mL gelatin concentration. The ratio of gelatin to glycerin was 1:0.4 and the drying conditions were 20 ℃ for 48 h. The thickness of the composite film was 0.36±0.01 cm, the percentage of breaking elongation was 50.56%±0.55%, the tensile strength was 27.81±0.22 N, and the permeability coefficient was 2.50±0.10 ×10−12 g·cm/(cm2·Pa·s), indicating that it had good mechanical properties. Compared with coating treatment, DPPH and ABTS+ free radical scavenging rates decreased by 18.95% and 19.84% after 15 d. The antibacterial zone diameter was 3±0.5 cm. Compared with the blank group and the coated group, the composite film could reduce the weight loss rate, inhibit the growth of TVB-N, maintain the color and extend the shelf life for 5 d. This study proved that microcapsule composite film with sea-buckthorn oil has good preservation effect, providing theoretical guidance for meat preservation.